2020
DOI: 10.30537/sijmb.v7i1.527
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Green Consumer Behavior the Mediating Role of Brand Image in the Cosmetic Industry

Abstract: In today’s world, the demand for cosmetic products is increasing at a faster rate than before, and companies have begun to manufacture cosmetic products to cater to the needs of local and international users. This paper aims to explore the relationship between celebrity endorsement, promotional activities, packaging, brand image, and green consumer buying behavior in the cosmetic industry of Pakistan. It also examines the mediating role of the brand image between celebrity endorsement and green consumer buying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…It is very important to check the adopted questionnaire reliability and validity before testing the proposed hypothesis in the research. In the present study three values are indicated in Table 1 such as items loading, Cronbach value and average variance extracted and based of these adopted questionnaire reliabilities and validly is confirmed [14]. The recommended value for the item loading and Cronbach alpha should be equal or greater than 0.70 [15].…”
Section: Questionnaire Reliability and Convergent Validitysupporting
confidence: 62%
“…It is very important to check the adopted questionnaire reliability and validity before testing the proposed hypothesis in the research. In the present study three values are indicated in Table 1 such as items loading, Cronbach value and average variance extracted and based of these adopted questionnaire reliabilities and validly is confirmed [14]. The recommended value for the item loading and Cronbach alpha should be equal or greater than 0.70 [15].…”
Section: Questionnaire Reliability and Convergent Validitysupporting
confidence: 62%
“…, 2020). Some studies have tried to find the influence of factors like celebrity endorsement, promotional activities, packaging and brand image, on green consumer buying behavior (Qalati et al. , 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Further, some studies on customers of organic eco-friendly beauty products did prove that gender, income level, education and profession have a major role in impacting consumers' purchasing behavior (Feil et al, 2020). Some studies have tried to find the influence of factors like celebrity endorsement, promotional activities, packaging and brand image, on green consumer buying behavior (Qalati et al, 2020). This research goes a step further to now look at the constructs adopted from the PMT and SOR theory to build a new model for predicting the purchase behavior of customers toward organic foods.…”
Section: Protection Motivation Theory (Pmt) and Stimulus-organism-res...mentioning
confidence: 99%
“…A study on electronics products in Taiwan concluded that "green brand image, green satisfaction, and green trust are positively related to green brand equity. " Thus, for sustainable growth and enhancing brand loyalty, firms should allocate considerable resources towards developing ecofriendly products (Qalati, Li, Mirani, Sohu, Hussain & Ahmed, 2020;Butt, Mushtaq, Afzal, Khong, Ong, & Ng, 2017).…”
Section: Green Brand Image and Green Buying Behaviormentioning
confidence: 99%